Investigation of Agro-concrete using by-products of Rice Husk in Mekong Delta of Vietnam. (2017) - Son, Nguyen Khanh; Toan, Nguyen Phung Anh; Dung, Tran Thi Thuy; Huynh, Nguyen Ngoc Tri
Abstract: Agro-concrete concept seems to create interesting links between agriculture sector and building industry. Over the last years, researcher around the world have reported their investigation on such material made out of different type of agricultural by-products mixed with lime-based binder. Based on the locally use natural aggregate and good thermo-physical properties, they are considered as as eco-material for more comfortable low carbon building. Indeed, energy efficiency or thermal conform are improved from optimization of building envelopes. In this paper, we focus on producing concrete block under mechanical compaction method from two types of rice husk (natural and reusing) mixing with binder (hydrate lime and metakaolin). Physio-mechanical properties of concrete block were characterized at appropriate period of curing condition in dry air. Empirical results show that both compressive strength and splitting strength of concrete block evolve over time due to pozzolanic reactivity and natural carbonation reaction. Low thermal conductivity 0.27 W/mK with normal density 880 kg/m3 in mixed formulation deal with the purpose of using in thermal and acoustic insulating solution. In the current context of rural development in the delta region, the objective of using rice husk concrete for non-load bearing wall building as filling material or non-fired brick would be discussed.